Effects of six sigma initiatives in Malaysian private hospitals - Ahmed, Selim; Abd. Manaf, Noor Hazilah; Islam, Rafikul (Emerald Group Publishing Ltd., 2019)
Purpose – This study aims to investigate applications of Six Sigma methodology in Malaysian private hospitals. It measures Six Sigma initiatives of the private hospitals based on demographics such as gender, position and working experience. Design/methodology/approach – The present study measures Six Sigma initiatives of private hospitals and used stratified random sampling to collect data from eight selected hospitals in Peninsular Malaysia. The respondents of the study include doctors, nurses, pharmacists and medical laboratory technologists. In this study, 520 questionnaires were distributed to respondents who are working in Malaysian private hospitals. In total, 251 responses were received (48.27 per cent response rate). The descriptive analysis, independent samples t-test and one-way ANOVA were undertaken using SPSS version 23. Findings – The findings of this study indicate that male respondents have better perception on four aspects of Six Sigma applications such as process improvement tools, process improvement methods, manage quality improvement activities and formal planning process compared to female respondents. The research findings also indicate that doctors have better perception regarding process improvement tools to measure quality improvement process, leadership to continuous improvement processes, training in process improvement tools for employees’ skill improvement compared to nurses, pharmacists, medical laboratory technologists. Research limitations/implications – The present research focussed solely on the Malaysian private hospitals, and thus the results might not be applicable to other countries. This study focussed on Six Sigma initiatives of private hospitals in Malaysia, while the future research may consider investigating the difference or conformance between private and public hospitals on Six Sigma initiatives and its relationship with quality performance. In addition, present study findings are expected to provide guidelines to enhance the applications of Six Sigma methodology in private hospitals in Malaysia as well as other countries. Originality/value – This research provides theoretical and practical contributions for the Six Sigma initiatives in private hospitals. Most of the past studies of Six Sigma initiatives are centred on manufacturing sector, but few empirical studies have been conducted on the health-care organisation. Thus, findings of the present study on the health-care sector contribute to the on-going pursuit of knowledge in the area of Six Sigma by using the strength of related theories and parent disciplines.